Effects of the use of information and communication technology (ICT) on students’ achievement in english lexis and structure (2010)
The study investigated the effects of use of Information and Communication Technology (ICT) on Students’ Achievement in English Lexis and Structure and also examined the effect of gender on Students’ Achievement in the use of Information and Communication Technology (ICT). Random sampling procedure was used to select 101 students, comprising 74 males and 29 females from six public and private co-educational secondary schools in Lagos State. The study, a survey research, posed three research questions. Instruments used for data collection include Lexis and Structure on ICT (ELLSICT) and Students' Questionnaire on use of ICT (SQUICT). The result showed that there is no significant effect of information and communication on Students' Achievement in English Language. The result also revealed that there is no significant gender difference in Students' Achievement in English Language in the Use of ICT. On the other hand, we discovered that there is a significant difference between Students' Achievement in English Language and their use of ICT in both private and public secondary schools in Lagos State.